Analysis of Youth Empowerment in Municipalities of Lithuania - Šukvietienė, Aušra; Šilalienė, Ilona (Socialiniai tyrimai, 2023)
An empowerment in the scientific literature is usually understood as the share of the power with civil society or its groups and/or creation of conditions for them to participate in governance processes with equal rights, in order to ensure the democratic governance that meets the needs of citizens. This article analyzes the situation of youth empowerment at the municipal level in Lithuania, highlighting the conditions for their involvement and the arising challenges since youth policy in Lithuania is implemented in accordance with the principles of subsidiarity. Seeking to reveal the problematic of the topic and to review previous studies, an analysis of scientific literature was carried out, and also, the analysis of secondary statistical data was carried out based on youth empowerment evaluation criteria set out in the Evaluation Methodology of the Implementation of the Youth Policy. Main issues at municipality level were identified by performing a qualitative study (structure interview) with the Coordinators of youth affairs of selected municipalities, responsible for the implementation of youth policy and representatives of youth non-governmental organizations in these municipalities. The conducted research allowed identifying further necessary improvements for youth empowerment at municipality level and measures that would contribute to creating more favourable conditions for youth participation.